School-Age Bullying, Workplace Bullying and Job Satisfaction: Experiences of LGB People in Britain - Nick Drydakis (Institute of Labor Economics (IZA), 2018)
Using a data set that contains information on retrospective school-age bullying, as well as on workplace bullying in the respondents' present job, the outcomes of this study suggest that bullying, when it is experienced by sexual orientation minorities tends to persist over time. According to the estimations, it seems that school-age bullying of LGB people is associated with victims' lower educational level and occupational sorting into non-white-collar jobs, especially for gay/bisexual men. In addition, the outputs suggest that for both gay/bisexual men and lesbian/bisexual women, school-age bullying is positively associated with workplace bullying and negatively associated with job satisfaction. Additional results suggest a negative association between workplace bullying and job satisfaction. However, the outcomes show a positive association between the existence of an LGBT group in the workplace and job satisfaction.
Keywords: J16; J28; J70; 330; school-age bullying; workplace bullying; job satisfaction; sexual orientation